The Effectiveness of Mometasone Spray and Triamcinolone Acetonide Gel in Preventing Sore Throat, Cough, and Hoarse after Intubation - Zentika. I. Fajri; Fredi Heru Irwanto; A Miarta; Theodorus (Journal of Anesthesiology and Clinical Research, 2021)
Background: Endotracheal intubation is a procedure performed by inserting an endotracheal tube into the airway. With endotracheal intubation, there can be several complications ranging from mild to severe. Sore throat, coughing, and hoarseness were several endotracheal intbation complications. From several studies, it was found that the incidence of POST was 21-65%. This study aimed to determine the efficacy between 0.1% triamcinolone acetonide gel and 100 mcg mometasone spray in reducing sore throat, cough, and hoarseness due to endotracheal intubation. Method: A Randomized Controlled Trial, Open-Label was carried out on patients undergoing endotracheal intubation with general anesthesia in RSMH operating room from September 2020 - November 2020. Seventy-two study subjects met the inclusion criteria and were divided into two groups, namely the triamcinolone acetonide gel group, and the mometasone spray group. Analyzing data was SPSS version 23. Result: There were no difference between age, sex, ASA PS classification, and length of operation between the two groups (p> 0.05). Mometasone spray 100 mcg and triamcinolone acetonide gel 0.1% had the same effectiveness to reduce endotracheal intubation such as sore throat, cough, and hoarseness within 24 hours of endotracheal intubation (p> 0.05). There was a significant difference in the incidence of sore throat between two groups in the first hour (p = 0.039). Conclusion: There was no statistically significant difference between the efficiency of mometasone spray 100 mcg and triamcinolone acetonide gel 0.1% on a sore throat, cough, and hoarseness within 24 hours of endotracheal intubation (p > 0.05).